The Role of Growth Opportunity and Internal Factor Toward Capital Structure of Manufacturing Company Member in Jakarta Islamic Index - Wafa Anggraeny; Robiyanto Robiyanto (International Journal of Social Science and Business, 2020)
The study aimed to analyze the factors that determined the capital structure of the manufacturing companies listed in the Jakarta Islamic Index (JII) from the period of 2015 to 2018. The independent variables in this study were profitability, asset structure, company size, and growth opportunity. The samples were taken by using the purposive sampling method and obtained 10 companies as research samples. Data analysis techniques use a regression analysis of data panel. The results of the regression panel in this study showed that profitability had a significant positive effect on capital structure. The asset structure, firm size and growth opportunity variables do not significantly influence the company's capital structure. This research implies that companies need to pay attention to profitability variable in determining capital structure.